Research on the Mobile CDN Integration Architecture in Virtualized EPC - Sufen Li; Hui Dong; Bingyi Fang; Yunyong Zhang; Jun Wu (Dianxin kexue)
Based on the current research on mobile CDN and core network virtualization, the method of deploying CND service nodes on virtualized EPC resources were discussed. First, the deployment solution of MCDN under the LTE was analyzed, as well as the virtualization solution of core net. Then a MCDN integration architecture was proposed on the basis of virtualized EPC resources, which can archive resources sharing and system expansion of MCDN service nodes by using virtualization technology and improve the reliability and efficiency of LTE and CDN.